Conceptual Metaphors in the 1945 Constitution of the Republic of Indonesia - Viani, Yetty Okta; Sidiq Budiawan, Raden Yusuf; Prayogi, Icuk (Balai Bahasa Kalimantan Tengah, 2024)
This research aims to describe the conceptual metaphor used in the 1945 Constitution of the Republic of Indonesia. This research method is descriptive qualitative. Data collection was carried out using the technique of listening and noting phrases, clauses and sentences contained in the 1945 Constitution of the Republic of Indonesia. The data analysis technique was in the form of the collection method using the language in question as a determining tool. Categorization was carried out on lingual units containing conceptual metaphors according to Lakoff and Johnson's theory. The research results show that the 1945 Constitution of the Republic of Indonesia uses conceptual metaphors which are categorized into structural metaphors, orientational metaphors and ontological metaphors. This conceptual metaphor data uses source domains related to humans, botany or plants, direction, travel, time, objects, dimensions and tools. The most frequently used metaphor is the structural metaphor. The implication of this research is that other concepts have been discovered that allow the 1945 Constitution of the Republic of Indonesia to be interpreted multiple times. So, understanding is needed in interpreting the values of the 1945 Constitution of the Republic of Indonesia. AbstrakTujuan dari penelitian ini ialah untuk mendeskripsikan metafora konseptual yang digunakan pada Undang-Undang Dasar Negara Republik Indonesia Tahun 1945. Metode penelitian yang digunakan adalah kualitatif deskriptif. Pengumpulan data dilakukan dengan teknik simak dan catat frasa, klausa, dan kalimat yang terdapat dalam Undang-Undang Dasar Negara Republik Indonesia Tahun 1945. Teknik analisis data berupa metode agih dengan bahasa yang bersangkutan sebagai alat penentu. Selanjutnya, dilakukan kategorisasi pada satuan lingual yang mengandung metafora konseptual sesuai dengan teori Lakoff dan Johnson. Hasil penelitian menunjukkan bahwa Undang-Undang Dasar Negara Republik Indonesia tahun 1945 menggunakan metafora konseptual yang dikategorisasikan menjadi metafora struktural, metafora orientasional, dan metafora ontologis. Data-data metafora konseptual itu menggunakan ranah sumber yang berkaitan dengan manusia, botani atau tanaman, arah, perjalanan, waktu, benda, dimensi, dan alat. Adapun metafora yang paling sering digunakan adalah metafora struktural. Implikasi penelitian ini adalah ditemukan konsep-konsep lain yang memungkinkan Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 menjadi multitafsir. Perlu pemahaman dalam menginterpretasikan nilai-nilai Undang-Undang Dasar Negara Republik Indonesia Tahun 1945.